Interplay between estrogen and Stat3/NF-κB-driven immunomodulation in lung cancer. (30th June 2020) - Deng, Shanshan; Ramos-Castaneda, Marco; Velasco, Walter V; Clowers, Michael J; Gutierrez, Berenice A; Noble, Oscar; Dong, Yiping; Zarghooni, Melody; Alvarado, Lucero; Caetano, Mauricio S; Yang, Shuanying; Ostrin, Edwin J; et al.
Abstract: K-ras mutant lung adenocarcinoma (LUAD) is the most common type of lung cancer, displays abysmal prognosis and is tightly linked to tumor-promoting inflammation, which is increasingly recognized as a target for therapeutic intervention. We have recently shown a gender-specific role for epithelial Stat3 signaling in the pathogenesis of K-ras mutant LUAD. The absence of epithelial Stat3 in male K-ras mutant mice (LR/Stat3 Δ/Δ mice) promoted tumorigenesis and induced a nuclear factor-kappaB (NF-κB)-driven pro-tumor immune response while reducing tumorigenesis and enhancing anti-tumor immunity in female counterparts. In the present study, we manipulated estrogen and NF-κB signaling to study the mechanisms underlying this intriguing gender-disparity. In LR/Stat3 Δ/Δ females, estrogen deprivation by bilateral oophorectomy resulted in higher tumor burden, an induction of NF-κB-driven immunosuppressive response, and reduced anti-tumor cytotoxicity, whereas estrogen replacement reversed these changes. On the other hand, exogenous estrogen in males successfully inhibited tumorigenesis, attenuated NF-κB-driven immunosuppression and boosted anti-tumor immunity. Mechanistically, genetic targeting of epithelial NF-κB activity resulted in reduced tumorigenesis and enhanced the anti-tumor immune response in LR/Stat3 Δ/Δ males, but not females. Our data suggest that estrogen exerts a context-specific anti-tumor effect through inhibiting NF-κB-driven tumor-promoting inflammation and provide insights into developing novel personalized therapeutic strategies for K-ras mutant LUAD. Abstract : Through lost- and gain-of-function studies, our data suggest that estrogen exerts a context-specific anti-tumor effect through inhibiting NF-κB-driven tumor-promoting inflammation and provide insights into developing novel personalized therapeutic strategies for K-ras mutant LUAD.